HIV/AIDS in the Caribbean : economic issues - impact and investment response - Theodore, Karl (UWI. Health Economics Unit St. AugustineTT, 2000)
Presents updated information on the estimated impact of HIV/AIDS on the economies of the Caribbean. Uses the output of a 1997 study on the economic impact of HIV/AIDS in Jamaica and Trinidad and Tobago as the starting point. Updates the projections for these two countries based on some adjustment to some of the underlying assumptions in respect of the epidemiology of the disease and the cost of treating infected persons.